"Producción y rentabilidad de tilapia (Oreochromia sp.l) mediante un sistema semi-intensivo en la comunidad Kichwa dumbiki del cantón Cascales Provincia de Sucumbios". - Qujiji Macías, Elvin Marcelo (2013)
The following summary details the study that was done about the production and profitability of tilapia (Oreochromis sp.) By means Semi - Intensive Dumbiki Kichwa community in the province of Sucumbios. Cascales Canton. In the upper part of the territory as you descend to the Amazon rainforest is modified due to the altitude, humidity and wind with an average temperature of 26 ° C, heavy rainfall throughout the year with an annual measure of 2000 mm, with a relative humidity between 85 to 90 % and an irregular topography, possessing an optimum location for the cultivation of tilapias to be surrounded by great rivers and estuaries and a clay loam soil recommended for cultivation. The general objective was raised in the project was to estimate the cost of production and profitability of tilapias in a system Semi-lntensive Dumbiki Kichwa community of Canton Cascales, Sucumbios province. Also raised three specific objectives which were: 1.- Estimate cost of production of tilapias in semi-intensive system of the Kichwa community Dumbiki. Province of Sucumbios of Canton Cascales, 2.- Evaluate the profitability in the production of tilapias in semi-intensive system's; Dumbiki, Kichwa Province of Sucumbios of Canton Cascales and 3.- Socialize families of Kichwa community of Canton Cascales-Dumbiki the economy of the benefits of the Province of Sucumbios in the implementation and production of tilapias, to help the Indian community and that lack of knowledge does not realize it. The study is conducted by the descriptive method through surveys which allow us to know the reality of the farmer and so, to get an idea of what the production and profitability of tilapia for which there was a 50 survey of the most relevant questions to determine the issue of same and conducted 69 interviews with farmers in the province of Sucumbios